Socialization in a Singaporean brokerage company : constructing the professional identity - Kang, Matthew (2015)
The professional broker occupies an important position in Singapore’s economy as a member of the financial industry playing a role in economic growth. Yet, for all his importance, it is difficult to identify who and what the professional broker is beyond the stereotypical ‘White-collared professional’ that generically refers to every professional. The principal argument in this paper analyses the socialization processes in a Singaporean Brokerage Company through Morrison’s Socialization Theory: Task Mastery, Role Clarification, Acculturation and Social Integration to understand how the professional broker is constructed. This study also investigates the cosmopolitan culture in the form of Language Skills and Dress Code, and studies the relationship between private-public aspects of selves of the professional identity. Qualitative interviews were conducted to analyse the socialization processes. Finally, the paper reviews the data according to Morrison’s framework, evaluating its limitations and discussing how and what professional brokerage identities are constructed through socialization.